THE IMPLEMENTATION OF CAMBRIDGE CURRICULUM ON BIOLOGICAL LEARNING IN GANDHI MEMORIAL INTERCONTINENTAL SCHOOL (GMIS) SEMARANG - Wijayanti, Jihan Sela; Susilowati, Sri Mulyani Endang; Isnaeni, Wiwi (FMIPA UNNES, 2019)
The aim to describe the implementation of biology learning and analyze the positive aspects of the curriculum in Gandhi Memorial Intercontinental School (GMIS) Semarang .The evaluation of this CIPP model used descriptive-qualitative approach. The variables were the Cambridge Curriculum with context, input, process, and product aspects. The data collection techniques used documentation, observation, and interviews. The data analysis method used triangulation. The research results showed that in context, the profile of GMIS Semarang has a background as an international school in accordance with government regulations. The input consists of students, curriculum, teachers, facilities and infrastructure, and teaching materials that fulfill the standards. The process consists of the implementation of  biology learning had a very good criteria which is 90% in the classroom and 92% practicum, the media was used as a support for learning, laboratories and library was used well. The assignments and teacher administration had been given well. The product in the form of student learning outcomes were good but it needed to be improved and the achievements that had been achieved by students at national and international levels were good. And there were positive aspects that can be applied to the national schools in improving the education quality.